AKTIVITAS ANTIBAKTERI SEDIAAN FOOT SANITIZER SPRAY YANG MENGANDUNG EKSTRAK BIJI KOPI DAN JAHE - Joko Santoso; Aldi Budi Riyanta (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
The smell of feet is one of the problems of some people caused by sweat mixed with bacteria and moist conditions. S.epidermis bacteria are bacteria that grow in these conditions. Coffee and ginger have synergistic benefits with strong aroma and antibacterial activity so it is preferred. This study is focused to determine the antibacterial inhibition of footsanitizer formula from a combination of coffee and ginger, and produce good physical properties. Maseration with 70% ethanol solvent was used in this study and then formulated. The formulation was evaluated for physical properties such as organoleptic test, pH test, clarity, specific gravity, viscosity. Antibacterial activity test using the well method on S.epidermis. The results showed that foot sanitizer formula had physical properties of clear liquid, distinctive smell of extract, cold taste and pH in accordance with the requirements of topical formulations. Formula III has the highest specific gravity, viscosity and with 0.954 g / ml and 2.3013 Cp. The highest antibacterial activity with 0.348 cm2Keywords: foot sanitizer spray, Coffee, Ginger, Antibacterial, S.epidermis